Impact of Six Extraction Methods on Molecular Composition and Antioxidant Activity of Polysaccharides from Young Hulless Barley Leaves - Mingming Wang; Chuangchuang Zhang; Yuting Xu; Mengting Ma; Tianming Yao; Zhongquan Sui (Foods, 2023)
Young hulless barley leaves are gaining recognition for potential health benefits, and the method of extracting polysaccharides from them is critical for potential food industry applications. This study delves into a comparative analysis of six distinct fiber extraction techniques: hot water extraction; high-pressure steam extraction; alkaline extraction; xylanase extraction; cellulase extraction; and combined xylanase and cellulase extraction. This analysis included a thorough comparison of polysaccharide–monosaccharide composition, structural properties, antioxidant activities (DPPH, ABTS, and FRAP), and rheological properties among fibers extracted using these methods. The results underscore that the combined enzymatic extraction method yielded the highest extraction yield (22.63%), while the rest of the methods yielded reasonable yields (~20%), except for hot water extraction (4.11%). Monosaccharide composition exhibited divergence across methods; alkaline extraction yielded a high abundance of xylose residues, whereas the three enzymatic methods demonstrated elevated galactose components. The extracted crude polysaccharides exhibited relatively low molecular weights, ranging from 5.919 × 104 Da to 3.773 × 105 Da across different extraction methods. Regarding antioxidant activities, alkaline extraction yielded the highest value in the ABTS assay, whereas enzymatically extracted polysaccharides, despite higher yield, demonstrated lower antioxidant capacity. In addition, enzymatically extracted polysaccharides exerted stronger shear thinning behavior and higher initial viscosity.